2017
DOI: 10.3389/fnbot.2017.00014
|View full text |Cite
|
Sign up to set email alerts
|

Fast Dynamical Coupling Enhances Frequency Adaptation of Oscillators for Robotic Locomotion Control

Abstract: Rhythmic neural signals serve as basis of many brain processes, in particular of locomotion control and generation of rhythmic movements. It has been found that specific neural circuits, named central pattern generators (CPGs), are able to autonomously produce such rhythmic activities. In order to tune, shape and coordinate the produced rhythmic activity, CPGs require sensory feedback, i.e., external signals. Nonlinear oscillators are a standard model of CPGs and are used in various robotic applications. A spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 48 publications
(62 reference statements)
0
33
0
Order By: Relevance
“…The CPG is a non-linear oscillator that works at a certain pattern frequency for different walking situations. The work by Nachstedt et al showed a frequency adaptation for the CPG [82]. By applying the pattern frequency adaptation, the system could detect and tolerate an external pattern frequency from the disturbances over a considerable length of time [83].…”
Section: Motion Path Controlmentioning
confidence: 99%
“…The CPG is a non-linear oscillator that works at a certain pattern frequency for different walking situations. The work by Nachstedt et al showed a frequency adaptation for the CPG [82]. By applying the pattern frequency adaptation, the system could detect and tolerate an external pattern frequency from the disturbances over a considerable length of time [83].…”
Section: Motion Path Controlmentioning
confidence: 99%
“…Frequency modulation (also known as entrainment, Buchli et al, 2006 ) uses feedback information to adapt the frequency of the CPG so that the frequencies of the feedback and the CPG are synchronized (Nachstedt et al, 2017 ). Usually, joint angle feedback is used for this process in robotics studies (Endo et al, 2004 ; Buchli and Ijspeert, 2008 ; Di Canio et al, 2016 ) and frequency modulation has been mainly employed for adaptations of locomotion speed (Harischandra et al, 2011 ; Di Canio et al, 2016 ) and body change (Ren et al, 2015 ).…”
Section: Key Factors and Mechanisms For Adaptive Interlimb Coordinmentioning
confidence: 99%
“…Due to the fundamental role of frequency in energy consumption, locomotion speed, and stability, the frequency-adaptation is extensively studied and applied in robotic systems [32,33]; especially in gait assistance and rehabilitation devices [34][35][36]. As another example, [37] shows that a simple frequency adaptation, through phaseresetting, can improve the gait-stability.…”
Section: Related Workmentioning
confidence: 99%